Pengaruh Penerimaan Pajak Daerah Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah Provinsi Sumatera Utara Periode 2019 -2022 - Handayani, Fitri; Sahputra, Juliandi; Widjaja, Natassia (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Funding for government administration can be carried out efficiently and effectively and to prevent overlap so that funding for government administration is regulated. The implementation of government authority which is the responsibility of the region is funded from the APBD, while the implementation of government authority which is the responsibility of the state is financed from the APBN. The failure to realize PAD in the North Sumatra regional government could be caused by several factors. In this research, researchers used regional taxes and regional levies to see how these two factors influence the achievement of Regional Original Income (PAD). The population used in this research is the entire original regional income of North Sumatra province during the 2019 – 2022 period of 33 provinces. The number of samples in this research was 33 conditions which were multiplied by 4 years of observation to obtain 132 research samples. The research results show that regional taxes have a significant influence on the Regional Original Income (PAD) of North Sumatra province in 2019-2022. Regional levies have an influence but are not significant on the Regional Original Income (PAD) of North Sumatra province in 2019-2022. Regional taxes and regional levies together influence the PAD of North Sumatra province in 2019-2022.